Advantages of diffuse light for horticultural production and perspectives for further research - Li, Tao; Yang, Qichang (Frontiers in Plant Science, 2015)
Plants use diffuse light more efficiently than direct light, which is well established due to diffuse light penetrates deeper into the canopy and photosynthetic rate of a single leaf shows a curvilinear response to the light flux density. Diffuse light also results in a more even horizontal and temporal light distribution in the canopy, which plays substantial role for crop photosynthesis enhancement as well as production improvement under diffuse light. Here we cover some of the recent findings about the effect of diffuse light on light distribution over the canopy and its direct and indirect effects on crop photosynthesis and plant growth, and suggest some perspectives for further research which could strengthen the scientific understanding of diffuse light modulate plant processes and its application in horticultural production.